PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN MATEMATIKA REALISTIK INDONESIA DI KELAS VIII SMP/MTS - Dela Amelia (Jurnal Edukasi dan Penelitian Matematika, 2021)
The purpose this research was to design a valid and practical student worksheet (LKPD) based on the Indonesian realistic mathematics education approach (PMRI) on system of linear equations of- two variables (SPLDV) material for class VIII SMP. This research is a development research using Plomp development, which consists of three phases, namely the preliminary research phase, the prototyping phase and the evaluation phase. Based on the results of data analysis from the feasibility aspect of content, language, presentation and graphics, the validity level of 82.79% was achieved with a very valid category. At the practical level of the LKPD obtained from questionnaires for students' answers, the practicality of 89.06% is in the very practical category. In view of the outcomes got, it tends to be presumed that the LKPD with PMRI SPLDV material in class VIII SMP can be proclaimed legitimate and functional Keywords— development Research, student Worksheet, Realistic mathematics education.